Clinical application of autologous fibroblast cell culture in gingival recession treatment. (16th July 2014) - Milinkovic, I.; Aleksic, Z.; Jankovic, S.; Popovic, O.; Bajic, M.; Cakic, S.; Lekovic, V.
Abstract : Background and Objective: Gingival recession is defined as soft and hard tissue displacement resulting in root surface exposure. The optimal outcome of gingival recession treatment is complete, predictable and long‐lasting root coverage with a significant level of tissue regeneration. Tissue engineering, which applies active regeneration principles, presents the contemporary treatment approach in the restitution and regeneration of lost tissues. The objective of the present study was to evaluate and compare the clinical results of application of an autologous fibroblast cell culture (AFCC) on a collagen matrix and a connective tissue graft (CTG) placed under a coronally advanced flap (CAF), in the treatment of single and multiple gingival recessions. Material and Methods: Eighteen patients from the Department of Periodontology, School of Dentistry, University of Belgrade, were randomly enrolled in this study. Inclusion criteria were the bilateral presence of Miller Class I or II single or multiple maxillary gingival recessions. A split‐mouth design was used in the study. The experimental group was treated with AFCC on a collagen scaffold, which was placed under a CAF. The control group received a combination of CTG and CAF. Clinical parameters such as gingival recession coverage, keratinized tissue width, clinical attachment level and gingival index were recorded at baseline and at 12 mo postoperatively. The oral hygiene level was assessed by plaque index evaluation. Postoperative healing was evaluated through the healing index, recorded 1, 2 and 3 wk postoperatively. The final esthetic outcome was assessed using the mean root coverage esthetic score (RES). Results: Statistically significant improvement of all parameters assessed was found compared with baseline. A statistically significant difference between groups was observed only in keratinized tissue width. Greater keratinized tissue width is still obtained with the use of CTG. Regarding the tissue‐healing results, no statistically significant difference was achieved. The RES results were similar for both groups. Conclusions: Within the limitations of the present study, both procedures proved to be efficient in gingival recession treatment. AFCC, as a novel tissue‐engineering concept and living cell‐based therapy, proved to be a reliable and successful treatment concept.